2022
DOI: 10.3389/fpsyt.2021.596017
|View full text |Cite
|
Sign up to set email alerts
|

The Cognitive-Enhancing Effects of Dendrobium nobile Lindl Extract in Sleep Deprivation-Induced Amnesic Mice

Abstract: Chronic sleep deprivation (SD) causes neurological and neurodegenerative dysfunction including learning and memory deficit. The orchid Dendrobium nobile Lindl (DNL), is widely used as a Yin tonic and medicinal food throughout Asia, and has many reported pharmacological effects. This study focused on the cognitive-enhancing effects of DNL in sleep deprivation-induced amnesia in mice and its biochemical mechanisms. Our results showed that the mice displayed significant cognitive deficits after 2-week SD while tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…However, there are still some limitations in the studies related to poor methodology in Chinese herbal medicine, such as complex chemical compositions and unclear efficacy that might be the result of the comprehensive action of all drug ingredients, which to some extent restrict clear conclusions. In addition, many other TCT treatments have also improved sleep disorders ( Cho et al, 2013 ; Bergdahl et al, 2017 ; Karadag et al, 2017 ; Li et al, 2018 ; Meng et al, 2018 ; Jiao et al, 2020 ; Hu et al, 2021 ; Jiang et al, 2021 ; Jiang et al, 2022a ; Jiang et al, 2022b ). Table 3 summarizes the effects of most TCT treatments on sleep disorders under different conditions.…”
Section: The Effect Of Traditional Chinese Therapy On Sleep Disordersmentioning
confidence: 99%
“…However, there are still some limitations in the studies related to poor methodology in Chinese herbal medicine, such as complex chemical compositions and unclear efficacy that might be the result of the comprehensive action of all drug ingredients, which to some extent restrict clear conclusions. In addition, many other TCT treatments have also improved sleep disorders ( Cho et al, 2013 ; Bergdahl et al, 2017 ; Karadag et al, 2017 ; Li et al, 2018 ; Meng et al, 2018 ; Jiao et al, 2020 ; Hu et al, 2021 ; Jiang et al, 2021 ; Jiang et al, 2022a ; Jiang et al, 2022b ). Table 3 summarizes the effects of most TCT treatments on sleep disorders under different conditions.…”
Section: The Effect Of Traditional Chinese Therapy On Sleep Disordersmentioning
confidence: 99%
“…As the treasure of China, traditional Chinese acupuncture has a long history, safety, and effectiveness, and has been widely respected in clinical application. A large number of animal experiments and related clinical studies have confirmed the safety and effect of acupuncture in the treatment of SD with cognitive dysfunction, [ 10 , 11 ] but the specific mechanism remains to be further explored.…”
Section: Introductionmentioning
confidence: 99%